Programa educativo de aprendizaje invertido para mejorar capacidades en lógica y conjuntos en estudiantes de la Facultad de Ciencias de la Educación y Humanidades Iquitos 2024 - Panduro Urrelo, Harvey Enrique (2025)
The study evaluated the effect of an educational program based on flipped learning on improving problem-solving abilities in logic and sets among university students at the Faculty of Education and Humanities in Iquitos, 2024. Employing an evaluative, longitudinal, univariate, and field-based design, the research involved a sample of 86 university students divided into an experimental group, who participated in the program, and a control group without intervention. A standardized test technique was used, and the instrument was a performance test validated by experts to collect data through pre- and post-tests administered to both groups. The findings revealed a significant improvement in the experimental group, whose average scores in solving problems related to logic and sets (17,22 ± 1,483) notably surpassed those of the control group (13,50 ± 1,483). These results demonstrate that the flipped learning program had a positive and significant impact on the development of mathematical skills, achieving the objectives set forth in the research.